Risma Nur - Risma Nur (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
Abstract: This study aims to determine the obstacles faced by elementary school teachers on the 2013 curriculum at SDN 7 Bangsri. This research uses a descriptive qualitative approach. To obtain information, researchers as the main instrument will be assisted with supporting instruments, namely instruments observation, interview, questionnaire and documentation. The research subjects were teachers who implemented the 2013 curriculum. Based on the analysis of the data obtained, the results showed that the obstacles experienced by elementary school teachers in implementing the 2013 curriculum came from the government or institutions and teachers. Constraints from the government include the distribution of books, assessment, teacher administration, time allocation, socialization, thematic learning implementation, curriculum implementation guidelines, and learning activities in student books. Obstacles from the teacher include the creation of instructional media, teacher understanding, integration of the content of the lessons in thematic learning, and mastery of information technology.